Efektifitas Video Berdialek Bahasa Jambi untuk Meningkatkan Pengetahuan tentang Penyakit HIV/AIDS pada Remaja di SMAN 8 Kabupaten Muaro Jambi - Suharti Suharti; Daryono Daryono (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The highest cumulative proportion of HIV / AIDS cases is at the age of 20-29 years (32.5%), 30-39 years (30.7%), 40-49 years (12.9%), 50-59 years (4.7 %), and finally 15-19 years of age (3.2%). This data indicates that adolescents 15-29 years are a vulnerable population and need to be targeted in the HIV AIDS prevention program in Indonesia and provide an illustration that adolescents need correct health information so as not to be infected by HIV. This study aims to improve adolescent knowledge through health education using video media. This research is a quasi-experimental research (quasi-experiment) that is providing health education about HIV / AIDS using video media. The videos used in this study are conventional HIV / AIDS videos and Jambi HIV / AIDS video dialogue. Data analysis uses bivariate analysis of T test for unpaired groups. The results showed that the average knowledge of students about HIV / AIDS after being given health education using Conventional Video media in SMA Negeri 8 Murao Jambi Regency in 2018 was 64.24. While the average knowledge of students about HIV / AIDS after being given health education using the Jambi Language Dialogic Video media in SMA Negeri 8 Muaro Jambi in 2018 was 76.44. There is a significant difference between respondents' knowledge given health education using conventional video media and using the Jambi Language Dialogic video media (p-values 0.00 and α 0.05). This means that the use of the Jambi Language Dialogic Video media is more effective than the Conventional Video media in providing information about HIV / AIDS to students of SMA Negeri 8 Muaro Jambi Regency in 2018.